Vertically Aligned Nanostructures for SOFC applications - Zamudio-García, Javier; Chiabrera, Francesco; Ramírez-Losilla, Enrique; Pryds, Nini; Esposito, Vincenzo; Marrero-López, David (My University, 2022)
One of the most recent strategies to enhance the electrode performance is preparing composite materials leading to an increase of the triple-phase-boundary (TPB) length. On this way, heteroepitaxial nanocomposite films such as vertically aligned nanostructures (VANs) deposited by Pulsed Laser Deposition (PLD) are one of the most promising and recent approaches to obtain nanocomposite active layers for energy applications1. In this work, thin films VANs based on (La0.8Sr0.2)0.98Fe0.8Ti0.2O3−δ-Ce0.9Gd0.1O1.95 (LSFT-GDC) electrodes were obtained for their use as functional layers in Solid Oxide Fuel Cells (SOFCs).
Keywords: Nanoestructuras; Electrodos; SOFC